Teaching strategies used by English First Additional Language teachers in teaching reading for comprehension - Dludla, Sifiso; Govender, Samantha; Mhlongo, Hlengiwe (Edelweiss Applied Science and Technology, 2024)
Reading is a fundamental skill essential for deep understanding and engagement across all subjects. This study explores Grade 6 teachers’ perspectives on strategies for teaching reading comprehension in the Intermediate Phase of English First Additional Language (EFAL). Using a multiple-case study design, it provides an in-depth exploration from various participants’ perspectives. The target population comprised Grade 6 EFAL teachers, with a purposeful sample of ten teachers from ten primary schools in the Nquthu circuit, uMzinyathi district, KwaZulu Natal, South Africa. Data collection methods included individual face-to-face semi-structured in-depth interviews and classroom observations, offering a comprehensive understanding of teachers’ classroom practices and strategies. The study reveals a significant gap between teachers’ reported strategies and their actual classroom practices. While teachers are aware of effective strategies such as guided reading, skimming and scanning, and the top-down approach, their implementation often reverts to traditional methods, highlighting the need for professional development. The findings emphasize the importance of aligning teaching practices with theoretical frameworks like Vygotsky’s Zone of Proximal Development to support learners effectively. Integrating assessments into the reading process is crucial for activating prior knowledge and confirming comprehension. Additionally, the study identifies a gap between teachers’ theoretical understanding and practical application of the Directed Reading Thinking Activity strategy. The study recommends bridging the gap between theory and practice through continuous professional development, practical training, and the availability of relevant resources to strengthen practices. Addressing these gaps can better foster reading comprehension skills, ultimately enhancing learners’ academic performance.